THE DYNAMICS OF DIGITAL SCHOOL LEADERSHIP: A CASE STUDY AT MTS ARRUKHSHATUL’ULUM - Badrudin, Badrudin; Fauzi, Helmi Al Hafid; Najuba, Hilyatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the dynamics of digital school leadership through a case study at MTSS Arrukhshatul’ulum, focusing on teacher involvement. The digital era presents unique challenges and opportunities in education, with school leadership playing a key role in navigating this transformation. The case study reveals that successful digital leadership involves close collaboration between the school principal and teachers. School principals need to have a deep understanding of educational technology and the ability to integrate it effectively into the learning strategy. The research findings highlight the crucial role of school principals in managing digital transformation at MTSS Arrukhshatul’ulum, prioritizing teacher interaction and involvement in the implementation of educational technology. Successful digital leadership also emphasizes the need for continuous training and support for teachers' technology skills. The practical implications of this research contribute to the development of effective leadership strategies for integrating technology in schools. The findings also suggest recommendations for educational institutions to adopt a responsive approach to technological developments, ensuring that teachers feel supported in adopting technology-based learning practices. Overall, this research illustrates how school leadership can successfully navigate the dynamics of the digital era by activating teachers as strategic partners. It provides valuable insights for education stakeholders looking to address challenges and harness the potential of educational technology in the future.